Angeborene Störungen im Lipoproteinstoffwechsel = Congenital disorders of lipoprotein metabolism - März, Winfried; Grammer, Tanja B.; Delgado Gonzales de Kleber, Graciela; Kleber, Marcus E. (Herz, 2017)
Congenital disorders of lipid metabolism are caused by a wide range of variants of the genes for receptors, apolipoproteins, enzymes, transfer factors, and cellular cholesterol transporters. Clinically most relevant are autosomal dominant familial hypercholesterolemia (FH) and familial combined hyperlipoproteinemia (FCHL). FH has a prevalence of 1:250. It is due to mutations of the low density lipoprotein (LDL) receptor, less often to mutations of the apolipoprotein B (APOB), the proprotein convertase subtilisin/kexin type 9 (PCSK9), or the signal transducing adapter family member 1 (STAP1). FH often leads to early atherosclerosis. Its diagnosis can definitely be made only by molecular genetic testing. The detection of mutations of the LDLR, APOB, or PCSK9 is an indicator for extremely high cardiovascular risk, independently of the concentration of LDL cholesterol. FCHL is also common (1:100) and is seen in about 10% of patients with early myocardial infarction. It is produced by combinations of frequent genetic variants affecting triglycerides and LDL cholesterol. Other monogenic hyperlipoproteinemias (HLP) affect the catabolism of chylomicrons (familial chylomicronemia) or of remnants of triglyceride-rich lipoproteins (type III hyperlipoproteinemia). Multiple hereditary disorders in HDL metabolism - with a broad spectrum of clinical significance - are known. Currently, second generation sequencing methods are used to simultaneously analyze multiple disease-causing genes. This approach cost-neutrally provides additional information such as the genetic risk of atherosclerosis and predisposition to statin intolerance.